Synthesis, characterization and biological evaluation of some glutathione inducing amino acid conjugates of valproic acid with reduced hepatotoxicity - Sinha S.K.; Praveen B.; Shrivastava P.K.; Shrivastava S.K. (My University, 2025)
Objective: To synthesis and evaluate three glutathione inducing amino acid conjugates of valproic acid (VPA) and compare with the same VPA to diminish its hepatotoxicity. Methods: Purified synthesised prodrugs were subjected to thin layer chromatography, melting point, solubility studies and characterised by UV, FTIR, 1H, 13C NMR and elemental analysis. The synthesised prodrugs were subjected to in vitro hydrolysis in various buffer solution (pH 1.2, 7.4, 9.0) and in vivo anticonvulsant, hepatotoxic activity studies. Result: Three synthesized conjugates were assumed to be in agreement with the anticipated structures. All the three conjugates were also able to prevent seizures in experimental rats with a comparable activity as the parent drug, VPA. Among the three conjugates, the glycine conjugate showed better anticonvulasant activity compared to glutamic acid and cystine conjugates. Conclusions: Significant reduction in hepatotoxicity and comparable anticonvulsant activities were obtained in all synthesised prodrugs as compared to VPA. © 2012 Asian Pacific Tropical Medicine Press.